Keep talking : communicative fluency activities for language teaching - Klippel, Friederike (Cambridge ; New York : Cambridge University Press, 2012)
This is a practical guide to communication activities in the language classroom, suitable for use with students from elementary to advanced level. Part I contains instructions for over 100 different exercises, including interviews, guessing games, jigsaw tasks, problem solving, values clarification techniques, mime, role play and story telling. For each activity, notes are also provided on the linguistic and educational aims, the level, organisation, time and preparation required. Part II contains the accompanying worksheets, which can be copied, making many of the activities instantly available for use in class. A comprehensive table of activities and an index are included for ease of reference
Introduction -- Questions and answers -- Discussions and decisions -- Stories and scenes
Translation of: Ideas
Includes bibliographical references
10
Keywords: Ingles -- Estudio y ensenanza; Langage et langues -- Etude et enseignement; Language and languages -- Study and teaching -- Problems, exercises, etc; Maitrise de la langue (Apprentissage d'une langue)